A cost-effectiveness analysis comparing the originator follitropin alfa to its biosimilars in patients undergoing a medically assisted reproduction program from a French perspective. (2nd January 2019) - Grynberg, Michaël; Murphy, Claire; Doré, Carole; Fresneau, Laurence; Paillet, Ségolène; Petrica, Nicoleta; Maurel, Frédérique; Ravonimbola, Harinala
Abstract: Objective: To assess the cost-effectiveness (CE) of the originator follitropin- α (Gonal-F) in patients undergoing a medically assisted reproduction (MAR) program in comparison to its biosimilars Bemfola and Ovaleap in a French context. Methods: A CE model was developed for France with a National Health Service (NHS) perspective. Clinical, safety, and dosage data were derived from pivotal clinical trials that compared Gonal-F to Ovaleap and Bemfola. Costs pertaining to drugs, hospitalizations, specialist visits, and examinations were retrieved from the French Programme de Médicalisation des Systèmes d'Information (PMSI) hospital database, literature review, and French clinical experts using 2017 Euro tariffs. In order to test the robustness of results, deterministic one-way sensitivity analyses were carried out on the main variables to assess the impact of treatment cost, probability of birth, ovarian hyperstimulation syndrome (OHSS) rates, and dosage. Results: The average incremental cost per live birth with OHSS and without OHSS was €259.56 and €278.39, respectively, for Gonal-F compared to the pooled biosimilars (i.e. Ovaleap and Bemfola). GONAL-F had an incremental efficacy of 0.06 over the pooled biosimilars. The incremental cost-effectiveness ratio for Gonal-F with OHSS ranged from €3, 274.80 to €4, 877.76 compared to the pooled biosimilars, owing to the additional live births reported with Gonal-F. Sensitivity analyses also supported results from the base case analyses, with Gonal-F being cost-effective or the dominant strategy in most cases. Conclusion: Gonal-F seems to be a cost-effective strategy compared to its biosimilars Ovaleap and Bemfola, irrespective of the incidence of OHSS events, but further data are needed to confirm these results.